Case Report: Neoadjuvant therapy with ripretinib for gastrointestinal stromal tumor: a case report - Liu, Guanmo; Zheng, Zicheng; Li, Jie; He, Yixuan; Zhang, Chenggang; Wang, Yihua; Kang, Weiming; Ye, Xin (Frontiers in Pharmacology, 2025)
Neoadjuvant therapy targeting genotype-specific gastrointestinal stromal tumors (GISTs) may be indicated in select cases. While the majority of patients respond to Imatinib with a reduction in tumor size, some exhibit either poor response or resistance, necessitating the exploration of alternative therapeutic strategies. This report describes a high-risk patient facing potential multiorgan resections whose tumor responded poorly after 14 months of Imatinib therapy. After 8 months of transitioning to Ripretinib treatment, there was a 26% reduction in the largest tumor diameter. This improvement allowed better delineation of the tumor from the surrounding tissues, which in turn made it possible to perform an R0 resection while preserving the possibly involved organs. To our knowledge, this is the first case report of Ripretinib as a neoadjuvant therapy for GIST with peripheral organ invasion to achieve complete resection. This case report may present the effectiveness of Ripretinib and introduce a relatively novel approach to clinical treatment.